Fourth Annual Report of the Board of Commissioners of the Central Park 106 (1861) - (:unkn) unknown (My University, 1861)
Prohibited any person from carrying firearms, throwing stones or other missiles within Central Park.
Keywords: CARRY - CERTAIN PUBLIC PLACES